Deeper - Gordon, Roderick; Williams, Brian James 1958-. (New York Chicken House/Scholastic, 2009)
As young archaeologist Will Burrows continues to search for his lost father in the strange underground world he has discovered beneath the city of London, he stumbles across a sinister plot with terrible implications for the world above.
"Published in the United Kingdom in 2008 by Chicken House ... Frome, Somerset"--Colophon.
Sequel to: Tunnels.
Keywords: Civilization, Subterranean -- Juvenile fiction; Missing persons -- Juvenile fiction; Archaeologists -- Juvenile fiction; Adventure stories; Underground areas -- Fiction; Missing persons -- Fiction; Adventure and adventurers -- Fiction; Archaeologists -- Fiction; London (England) -- Juvenile fiction; London (England) -- Fiction; Young adult fiction